Etnopemodelan Matematika Nada Terhadap Ukuran Instrumen Alat Musik Calung Banyumas - Novenda, Elizabeth Eristya; Waruwu, Bryan Marthinus; Agustin, Dhea Puspita Putri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Calung is a musical instrument originating from West Java, apart from West Java, Calung is also developing in other areas, one of which is Banyumas. Based on the shape and size, the researcher saw the relevance of this instrument with several mathematical concepts. For this reason, researchers want to see mathematical modeling based on size in Calung Banyumas. The results obtained are that the length, diameter and frequency of the slendro gambang, slendro dhendhem and slendro kenong barrels have a pattern. This pattern forms a function, the most appropriate function is the exponential. This obtained function can be used to predict the size needed to create the desired frequency.